Development of Film Music in Ukraine in the 1920’s - Kostogryz, Sergii; Myslavskyi, Volodymyr; Cherkasova, Nataliia (Journal of History Culture and Art Research, 2020)
The objective of this study is to explore the interactions between music and films, the progress, styles, forms, and means of film scoring, as well as to analyze the trends in the development of film music in Ukraine in the 1920s. The article outlines the array of challenges associated with the formation of various approaches to film scoring in the Ukrainian cinematography. Different styles and forms of film scoring molded in the 1920s in USSR in general, and in Ukraine in particular, are investigated. Analysis of the contemporaries’ debate in specialized magazines showed that three types of film scoring prevailed at those times: improvisation (music reflects the external action of the movie, the atmosphere where that action is happening); compilation (music is used as an illustrative tool to render the sentiment of each separate episode, without plotting a seamless musical piece for the entire movie); and composition (thematic musical illustration for the entire movie). The article also addresses major means of musical scoring for cinema shows — “complex”, “orchestra”, “piano”.